Effect of surface patterning on frictional heating of vitamin E blended UHMWPE - Sagbas, B.; Durakbasa, M. N. (ELSEVIER SCIENCE SA, 2013)
Friction between articulating surfaces cause temperature rise in the acetabular cup and femoral head. This heating may influence the rate of wear, fatigue, creep and oxidative degradation of bearing materials. The objective of this study is to determine the effect of surface patterning on frictional temperature rise of the articulating surfaces of vitamin E blended ultra-high molecular weight polyethylene acetabular component paired with a cobalt-chromium (CoCrMo) femoral component. For this reason concave dimples were formed on inner surface of the acetabular cup with 0.5 mm diameter and 0.5 mm depth. Temperature rise between the bearing surfaces was measured under different loading conditions. Frictional measurements of the joints were carried out on a custom made hip joint friction experimental set up. The prostheses were of 28 mm diameter. Applied static loads were changed from 200 N to 1500 N. In the flexion-extension plane, a simple harmonic oscillatory motion between +/- 24 degrees was applied to the ultra high molecular weight polyethylene acetabular component. The frequency of motion was 1 Hz and the tests were run up to 11,000 cycles. Temperature rise in acetabular and femoral component was recorded with embedded thermocouples. Lower temperature rise in patterned sample pairs were measured than unpatterned samples. So it can be said that the surface patterning contributes to reduction of frictional heating of sliding surfaces. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Hip joints; Friction; Frictional heating; Frictional temperature; Surface patterning; TOTAL KNEE REPLACEMENT; TOTAL HIP IMPLANTS; POLYETHYLENE CUPS; ALPHA-TOCOPHEROL; WEAR; REDUCTION; COMPONENTS; RESISTANCE; BEHAVIOR; CRACKING; Engineering; Materials Science